2021
DOI: 10.3348/kjr.2020.1262
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Radiofrequency Data Analysis for the Assessment of Hepatic Steatosis in Nonalcoholic Fatty Liver Disease Using Magnetic Resonance Imaging Proton Density Fat Fraction as the Reference Standard

Abstract: Objective To investigate the diagnostic performance of quantitative ultrasound (US) parameters for the assessment of hepatic steatosis in patients with nonalcoholic fatty liver disease (NAFLD) using magnetic resonance imaging proton density fat fraction (MRI-PDFF) as the reference standard. Materials and Methods In this single-center prospective study, 120 patients with clinically suspected NAFLD were enrolled between March 2019 and January 2020. The participants underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 35 publications
6
45
1
Order By: Relevance
“…In several recent studies, AC calculated with these techniques generally showed a good diagnostic performance for hepatic steatosis, with liver biopsy or MRI-PDFF as reference standards (AUROC, 0.76–0.98 with different techniques, reference standards, and target degree of steatosis) [ 20 21 22 91 92 93 94 95 96 97 98 ]. In addition, AC has been shown to correlate well with the degree of steatosis evaluated by histology or MRI-PDFF ( r = 0.47–0.78) [ 20 21 22 91 92 93 94 95 96 97 ]. The detailed results of the studies on ATI, UGAP, ATT, and TAI are summarized in Table 3 and Figure 4B .…”
Section: Qus Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In several recent studies, AC calculated with these techniques generally showed a good diagnostic performance for hepatic steatosis, with liver biopsy or MRI-PDFF as reference standards (AUROC, 0.76–0.98 with different techniques, reference standards, and target degree of steatosis) [ 20 21 22 91 92 93 94 95 96 97 98 ]. In addition, AC has been shown to correlate well with the degree of steatosis evaluated by histology or MRI-PDFF ( r = 0.47–0.78) [ 20 21 22 91 92 93 94 95 96 97 ]. The detailed results of the studies on ATI, UGAP, ATT, and TAI are summarized in Table 3 and Figure 4B .…”
Section: Qus Techniquesmentioning
confidence: 99%
“…However, AC can also theoretically be affected by fibrosis, although the effect of fibrosis is less pronounced than steatosis [ 20 ]. Different results have been reported on the effects of hepatic fibrosis on AC measured with ATI, UGAP, or TAI [ 92 93 97 100 101 ]. Therefore, further studies and standardization of AC, with consideration of concurrent hepatic fibrosis, are warranted.…”
Section: Qus Techniquesmentioning
confidence: 99%
“…However, the 95% LOAs of the absolute difference in mean AC values were quite large and were thought to be clinically unacceptable (-0.22 to 0.11 for ATI and TAI, from -0.17 to 0.18 for ATI and UGAP, and from -0.08 to 0.20 for TAI and UGAP). Many previous studies have reported the high diagnostic performance of ultrasound attenuation imaging for diagnosing hepatic steatosis and grading severity, but there is a wide variation in optimal cut-off values for diagnosing hepatic steatosis reported in each study, ranging from 0.59 to 0.69 for ATI (0.59 to 0.69 for MRI-PDFF as reference standard; 0.64 to 0.69 for histopathology as reference standard); for 0.88 for TAI (MRI-PDFF as reference standard), and from 0.53 to 0.60 for UGAP (0.53 for histopathology as reference standard; 0.60 for MRI-PDFF as reference standard [20][21][22]30]. Moreover, the optimal cut-off values for discriminating each grade of hepatic steatosis (mild [S1], moderate [S2], and severe [S3]) showed minimal gaps (range, 0.02-0.10) [20][21][22]30].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Many previous studies have reported the high diagnostic performance of ultrasound attenuation imaging for diagnosing hepatic steatosis and grading severity, but there is a wide variation in optimal cut-off values for diagnosing hepatic steatosis reported in each study, ranging from 0.59 to 0.69 for ATI (0.59 to 0.69 for MRI-PDFF as reference standard; 0.64 to 0.69 for histopathology as reference standard); for 0.88 for TAI (MRI-PDFF as reference standard), and from 0.53 to 0.60 for UGAP (0.53 for histopathology as reference standard; 0.60 for MRI-PDFF as reference standard [20][21][22]30]. Moreover, the optimal cut-off values for discriminating each grade of hepatic steatosis (mild [S1], moderate [S2], and severe [S3]) showed minimal gaps (range, 0.02-0.10) [20][21][22]30]. Considering the minimal gradual change in AC values according to the grade of hepatic steatosis, the calculated 95% LOAs of the absolute difference in AC values in our study were thought to be too large to be clinically acceptable.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation